SDN: Evolution and Opportunities in the Development IoT Applications - Ángel Leonardo Valdivieso Caraguay; Alberto Benito Peral; Lorena Isabel Barona López; Luis Javier García Villalba (International Journal of Distributed Sensor Networks, 2014)
The exponential growth of devices connected to the network has resulted in the development of new IoT applications and on-line services. However, these advances are limited by the rigidity of the current network infrastructure, in which the administrator has to implement high-level network policies adapting and configuring protocols manually and usually through a command line interface (CLI). At this point, Software-Defined Networking (SDN) appears as a viable alternative network architecture that allows for programming the network and opening the possibility of creating new services and more efficient applications to cover the actual requirements. In this paper, we describe this new technology and analyze its opportunities in the development of IoT applications. Similarly, we present the first applications and projects based on this technology. Finally, we discuss the issues and challenges in its implementation.